Enantioselective Michael/Hemiketalization Cascade Reactions between Hydroxymaleimides and 2-Hydroxynitrostyrenes for the Construction of Chiral Chroman-Fused Pyrrolidinediones - Dong-Hua Xie; Cheng Niu; Da-Ming Du (Molecules, 2022)
In this paper, the organocatalytic asymmetric Michael addition/hemiketalization cascade reactions between hydroxymaleimides and 2-hydroxynitrostyrenes were developed, which provided a new protocol for building a chiral ring-fused chroman skeleton. This squaramide-catalyzed cascade reaction provided chiral chroman-fused pyrrolidinediones with three contiguous stereocenters in good to high yields (up to 88%), with excellent diastereoselectivities (up to >20:1 dr) and enantioselectivities (up to 96% ee) at −16 °C. Moreover, a scale-up synthesis was also carried out, and a possible reaction mechanism was proposed.